Reversibility of renal impairment in patients with multiple myeloma treated with bortezomib-based regimens: identification of predictive factors. - Dimopoulos, M.A.; Roussou, M.; Gavriatopoulou, M.; Zagouri, F.; Migkou, M.; Matsouka, C.; Barbarousi, D.; Christoulas, D.; Primenou, E.; Grapsa, I.; Terpos, E.; Kastritis, E. (Clinical lymphoma & myeloma, 2009)
PURPOSE: Renal impairment is a frequent complication of multiple myeloma (MM) and is associated with significant morbidity and increased early death rate. Bortezomib is active and well tolerated in patients with MM who present or develop renal impairment. PATIENTS AND METHODS: We analyzed 46 consecutive patients who presented with renal impairment in order to evaluate the impact of bortezomib on the improvement of renal function and to identify predictive factors associated with renal response. All patients received bortezomib with dexamethasone with or without other agents. RESULTS: Renal response was documented in 59% of patients within a median of 11 days (range, 8-41 days). Two of 9 patients who required dialysis became dialysis independent. A complete renal response (CRrenal) was documented in 30% of patients. Toxicities were similar to those seen in myeloma patients without renal failure who were treated with bortezomib-based regimens. Patients with light chain-only myeloma had a higher probability of achieving a renal response, and previously untreated patients had a higher probability for complete resolution of renal impairment, while light chain-only myeloma was independently associated with a shorter time to renal response. The degree of renal impairment was not predictive of the probability for renal response or CRrenal; however, in a subset of patients for whom cystatin C was available, a baseline cystatin C > 2 mg/L or cystatin C calculated estimated glomerular filtration rate < 30 mL/min were associated with a lower probability of CRrenal. CONCLUSION: We conclude that bortezomib-based regimens may improve renal function in the majority of myeloma patients with renal impairment.